EU 2020 - Social impact of the new form of European governance - Pochet, Philippe (Brussels, 2010)
"This issue of the Policy Brief - European Social Policy concerns the strong and potentially negative impact of the new forms of monetary and economic governance on employment and on social policies.The author, Philippe Pochet,General Director of the ETUI, argues that this impact will be channelled by the new governance nexus of the EU2020/Stability and Growth Pact, but also by the return to a very liberal definition of the drivers of growth and by a new definition of EU social policy. However, this policy brief also shows that much will depend on the strategy adopted by the relevant political and social actors."